IMPLEMENTASI ASPEK DIGITAL MARKETING PADA INOVASI “e-KATALOG UMKM KECAMATAN PORONG KABUPATEN SIDOARJO” DALAM RANGKA MENDUKUNG PERTUMBUHAN EKONOMI - Imambang Eka Sulistya; Ahmad Thohir; Novita Budirahayu; Ria Ayu Ningtyas (Universitas Udayana, 2023)
This authorship was motivated by the problems of economic development in Sidoarjo Regency during the Covid-19 pandemic, especially those that afflicted MSME actors. The economy in Sidoarjo Regency during the Covid-19 pandemic experienced negative economic growth, regional disparities, and MSME marketing problems. The data used is secondary data. The secondary data was obtained through literature study. The analysis technique used is qualitative descriptive, while the method used is Science and Technology Diffusion. The result of this writing is that Porong District succeeded in creating an innovation